1996
DOI: 10.1046/j.1526-4610.1996.3607442.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dyspeptic Syndrome in Migraine: Morphofunctional Evaluation on 53 Patients

Abstract: The authors, in order to evaluate the important role of gastrointestinal dysfunction during the migraine attack, have studied 53 patients with migraine without aura during the asymptomatic stage between attacks. Patients were examined functionally with a pH meter test of the gastroesophageal tract over 24 hours and morphologically with esophagogastroduodenoscopy. The results of this study point out that in a high percentage of patients with migraine, both evaluations are normal. The authors suggest the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 4 publications
2
11
0
Order By: Relevance
“…Various gastrointestinal symptoms, such as nausea, vomiting, retching, and loss of appetite are characteristic of patients with migraine. In addition, migraine can be accompanied by a sense of heaviness in the epigastric region, epigastric pain, belching, and lower gastrointestinal symptoms, such as diarrhea and flatulence 2. The positive correlation between migraine and the presenece of symptoms consistent with functional gastrointestinal disorders (FGIDs) has previously been established in many clinical observations and epidemiological studies 2-6.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Various gastrointestinal symptoms, such as nausea, vomiting, retching, and loss of appetite are characteristic of patients with migraine. In addition, migraine can be accompanied by a sense of heaviness in the epigastric region, epigastric pain, belching, and lower gastrointestinal symptoms, such as diarrhea and flatulence 2. The positive correlation between migraine and the presenece of symptoms consistent with functional gastrointestinal disorders (FGIDs) has previously been established in many clinical observations and epidemiological studies 2-6.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, migraine can be accompanied by a sense of heaviness in the epigastric region, epigastric pain, belching, and lower gastrointestinal symptoms, such as diarrhea and flatulence 2. The positive correlation between migraine and the presenece of symptoms consistent with functional gastrointestinal disorders (FGIDs) has previously been established in many clinical observations and epidemiological studies 2-6. A recent large, population-based, cross-sectional study reported a higher prevalence of headache, including migraine, in individuals with reflux symptoms, diarrhea, constipation, or nausea than in individuals without such complaints 5.…”
Section: Introductionmentioning
confidence: 99%
“…Migraine and headache are frequently reported by patients with gastrointestinal (GI) symptoms such as nausea, vomiting, retching, abdominal pain, and food intolerance 9-11. Among these symptoms, nausea and vomiting are the most common GI symptoms associated with migraine.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies are published on prevalence of endoscopic and gastrointestinal histopathologic findings among patients with migraine. 50 - 52 These studies reported a high prevalence of gastritis in the antrum or gastric corpus, and duodenitis among migraine sufferers. 50 - 52 The main problem in these studies is not excluding patients on analgesics.…”
Section: Discussionmentioning
confidence: 99%
“… 50 - 52 These studies reported a high prevalence of gastritis in the antrum or gastric corpus, and duodenitis among migraine sufferers. 50 - 52 The main problem in these studies is not excluding patients on analgesics. In our study, the endoscopic and pathologic findings were not statistically significant between migraine and non-migraine groups except for the presence of hiatal hernia.…”
Section: Discussionmentioning
confidence: 99%